Does thermal time for germination vary among populations of a tree legume (Peltophorum dubium)? - L. F. D. Andrade; V. J. M. Cardoso (Brazilian Journal of Biology)
Abstract Few works report the use of degree-days (DD) – used in crops to predict events and schedule management activities – to describe the germination of tropical trees. The cardinal temperatures (base, optimum and ceiling temperature) for germination of the species may vary depending on the seed provenance. Peltophorum dubium (Spreng.) Taub. is an early successional leguminous tree widely distributed in South America, often occurring as cultivated or naturalized trees, thus considered to be a good example for testing DD model in tree species. The main objective of this study was to describe the seed germination response of different populations of P. dubium as function of DD accumulation during germination assays in semi-controlled (fluctuating temperatures) conditions. Germination assays with manually scarified seeds sown in aluminum sheet trays filled with a composed substrate were performed under greenhouse conditions at different times. Three methods were employed in order to describe the accumulation of thermal time throughout the assays and, considering the seed lot and sowing time, a trapezoid area method was relatively more effective in describing the germination. The germination curves of P. dubium seeds from different populations, expressed in degree-days estimated directly from temperature records schedules, tend to be more clustered suggesting little variation among thermal time requirements in different seed provenances. Otherwise, the thermal time requirement can vary depending on the time of sowing, and any increase in DD requirement when the assays were performed under higher mean temperatures can be related to a thermal effect on the germination of scarified seeds.